PERAN PROMOSI MEDIA SOSIAL DAN PENDAMPINGAN KEWIRAUSAHAAN DALAM MENINGKATKAN PERTUMBUHAN USAHA PENGUSAHA MUDA DI SURABAYA (STUDI KASUS KADIN SURABAYA) - Alfian Nur Al Mubarok; Maryam Bte Badrul Munir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the roles of social media promotion and KADIN’s entrepreneurship mentoring in supporting the business growth of young entrepreneurs in Surabaya. A qualitative approach with a descriptive research design was employed. The study's informants consisted of young entrepreneurs affiliated with KADIN. Data collection was conducted through in-depth interviews, observation, and documentation. Data analysis utilized the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and theory triangulation. The results indicate that social media promotion plays a role in enhancing brand awareness, expanding market reach, boosting business credibility, and establishing business identity. Entrepreneurship mentoring provided by KADIN contributes to enhancing the capacity of young entrepreneurs through training, mentoring, and the strengthening of business networks. Furthermore, networking serves as social capital that supports business growth by expanding relationships and business opportunities. Business growth is characterized not only by increased revenue but also by growth in the customer base, business networks, and new business opportunities. This study concludes that the business growth of young entrepreneurs in Surabaya is influenced by a combination of social media promotion, entrepreneurship mentoring, and social capital gained through entrepreneurship organizations.